The Relative Returns to Education, Experience, and Attractiveness for Young Workers - Emily A. Beam; Joshua Hyman; Caroline Theoharides (Institute of Labor Economics (IZA), 2017)
Understanding employer preferences for characteristics of young workers is crucial to designing effective policies to reduce youth unemployment in developing countries. We conduct a randomized resume audit study, simultaneously examining the returns to education, experience, and physical attractiveness among young workers applying for entry-level jobs in a developing country context. Employers do not value college experience without a degree. Postsecondary vocational training increases the likelihood of a callback, but only for blue-collar occupations typically offered only to male workers. Work experience is valued across most occupations; however, among service-sector jobs with in-person customer interactions, attractive applicants receive 23 percent more callbacks, swamping the returns to experience. Our results can guide policymakers in the design of labor market programs to reduce youth unemployment as well as help young workers make optimal choices to ease their school-to-work transition.
Keywords: J23; J24; J70; C93; 330; returns to education; school-to-work transition; audit study; labor demand; returns to experience; attractiveness